2016
DOI: 10.1016/j.disc.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

A generalization of carries process and riffle shuffles

Abstract: As a continuation to our previous work [7], we consider a generalization of carries process. Our results are : (i) right eigenvectors of the transition probability matrix, (ii) correlation of carries between different steps, and (iii) generalized riffle shuffle whose corresponding descent process has the same distribution as that of the generalized carries process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Then formulas in Theorems 1.1, 1.3 follows from Lindeström-Gessel-Viennot lemma [8,6]. This bijection is the same as that between a generalized carries process called (b, n, p)-carries process, and the descent process of the random walk generated by (b, n, p)-shuffle, discussed in [12]. The contents of later sections are outlined as follows.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Then formulas in Theorems 1.1, 1.3 follows from Lindeström-Gessel-Viennot lemma [8,6]. This bijection is the same as that between a generalized carries process called (b, n, p)-carries process, and the descent process of the random walk generated by (b, n, p)-shuffle, discussed in [12]. The contents of later sections are outlined as follows.…”
Section: Introductionmentioning
confidence: 83%
“…Diaconis-Fulman [3,4] showed that the descent process of this random walk is a Markov chain which has the same distribution as that of the carries process in adding numbers studied by Holte [7]. The authors in this paper previously considered a generalized riffle shuffle on the colored permutation group G p,n , and a generalized carries process and showed that the descent process of the former has the same distribution as the latter [11,12]. In this paper, we study the generalized riffle shuffle studied in [12] and derive a formula for the probability of finding descents at given positions.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations